A dog's way home [compact disc, unabridged] - Cameron, W. Bruce (Tantor Media, 2017)
Lucas Ray is shocked when an adorable puppy jumps out of an abandoned building and into his arms. Though the apartment he shares with his mother, a disabled veteran, doesn't allow dogs, Lucas can't resist taking Bella home. Bella is inexplicably drawn to Lucas, even if she doesn't understand the necessity of games like No Barks. As it becomes more difficult to hide her from the neighbors, Lucas begins to sneak Bella into the VA where he works. There, Bella brings joy and comfort where it is needed most. After Bella is picked up by Animal Control because pit bulls are banned in Denver, Lucas has no choice but to send her to a foster home until he can figure out what to do. But Bella, distraught at the separation, doesn't plan to wait. With four hundred miles of dangerous Colorado wilderness between her and her person, Bella sets off on a seemingly impossible and completely unforgettable adventure home.